Growing Uniform Graphene Disks and Films on Molten Glass for Heating Devices and Cell Culture. (20th October 2015) - Chen, Yubin; Sun, Jingyu; Gao, Junfeng; Du, Feng; Han, Qi; Nie, Yufeng; Chen, Zhaolong; Bachmatiuk, Alicja; Priydarshi, Manish Kr.; Ma, Donglin; Song, Xiuju; Wu, Xiaosong; et al.
Abstract : The direct growth of uniform graphene disks and their continuous film is achieved by exploiting the molten state of glass. The use of molten glass enables highly uniform nucleation and an enhanced growth rate (tenfold) of graphene, as compared to those scenarios on commonly used insulating solids. The obtained graphene glasses show promising application potentials in daily‐life scenarios such as smart heating devices and biocompatible cell‐culture mediums.